2014
DOI: 10.4196/kjpp.2014.18.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulatory Effect of Essential Fatty Acids on Glucose Uptake Involves Both Akt and AMPK Activation in C2C12 Skeletal Muscle Cells

Abstract: Essential fatty acid (EFA) is known to be required for the body to function normally and healthily. However, the effect of EFA on glucose uptake in skeletal muscle has not yet been fully investigated. In this study, we examined the effect of two EFAs, linoleic acid (LA) and α-linolenic acid (ALA), on glucose uptake of C2C12 skeletal muscle cells and investigated the mechanism underlying the stimulatory effect of polyunsaturated EFAs in comparison with monounsaturated oleic acid (OA). In palmitic acid (PA)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Specifically, palmitic acid, alpha-Monopalmitin, and/or Beta-Monopalmitin were found at each time found (Supplemental Table 1). Recent studies have demonstrated that the essential fatty acids linoleic acid (LA) and alpha-linolenic acid (ALA) themselves can improve glucose uptake in C2C12 cells made insulin resistant using palmitic acid 39 , making the balance between fatty acids and glucose critically important when modeling myocytes in vitro.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Specifically, palmitic acid, alpha-Monopalmitin, and/or Beta-Monopalmitin were found at each time found (Supplemental Table 1). Recent studies have demonstrated that the essential fatty acids linoleic acid (LA) and alpha-linolenic acid (ALA) themselves can improve glucose uptake in C2C12 cells made insulin resistant using palmitic acid 39 , making the balance between fatty acids and glucose critically important when modeling myocytes in vitro.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Also, a positive control, metformin did not show any cytotoxicity up to 1 mM on C2C12 cells (data not shown). In previous reports, metformin at concentration of 1 mM has no toxicity and commonly used on C2C12 cells (Bruckbauer and Zemel, 2013;Park et al, 2014). Therefore, we used metformin at concentration of 1 mM and icariin at concentrations of 100 μM or less for subsequent studies.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, an independent study by Tardif and co‐workers demonstrated that aged rats fed an oleate‐enriched diet display marked improvements in insulin sensitivity as well as increased muscle protein synthesis, concomitant with increased expression of genes implicated in stimulating mitochondrial β‐oxidation including peroxisome proliferator‐activated receptor (PPAR)α and PPARβ, as well as CPT‐1β . Moreover, C2C12 myotubes treated with the PUFAs linolenic acid and ALA have been shown to exhibit increased activation of AMPK, another key positive regulator of mitochondrial β‐oxidation . In addition, DHA has also been reported to inhibit protein degradation in C2C12 myotubes through a PPARγ‐dependent pathway .…”
Section: Role Of Unsaturated Fatty Acids In Maintaining Skeletal Muscmentioning
confidence: 96%